A range-free localisation algorithm based on connectivity in wireless sensor networks. (2016) - Liu, Liping; Chu, Chunliang; Xia, Feng
Sensor nodes' position is very important in many wireless sensor networks (WSNs) applications. In this paper, a novel range-free localisation algorithm based on connectivity (LAC) is proposed. By exploiting the probabilistic regulation in cluster-based deployment, the theoretical number of a sensor's neighbours from certain cluster is determined by distance between the sensor and the corresponding cluster head. So distances between sensors and cluster heads can be derived by minimising the deviation between the theoretical number of neighbour sensors and the measurement. Using the optimal distance to each cluster head, the position of each sensor can be estimated with maximum likelihood (ML) multilateration. Compared with some existing range-free algorithms, LAC performs better in terms of localisation accuracy, especially in beacon-less scenarios and reduces communication overhead and computation complexity to some extent. Extensive simulations are performed and the results are observed to be in good consistence with theoretical analysis.